PENERAPAN TEKNOLOGI DAN MANAJEMEN USAHA UNTUK MENINGKATKAN EFEKTIFITAS DAN EFISIENSI PRODUKSI SERTA KEUNTUNGAN PADA IKM KERUPUK PETHULO - Wendy Triadji Nugroho; Naning Retnowati (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2016)
Both of home industries in this Social Responsibility Program (IbM) are located in Kecamatan Rambipuji Kabupaten Jember. Our IbM patners are Mr. Ngatijo and Mr. Kholik. They are the ownwer of Kerupuk Pethulo Home Industries. The purpose of this activities are :1) to increase the effectiveness and efficiency of their production process by giving some production machines), and 2)to train them about business and marketing management. These activities give the good impact for them. They can increase the effectiveness and efficiency of their production process. They also having an important knowledge about how to manage business for reaching much profit and knowing how to apply  the marketing strategy for getting many customers.